Visual guide to options - Levy, Jared, 1976- (Hoboken, New Jersey : Bloomberg Press, 2013)
The practical, visual guide to the complex world of options investing loaded with tactics and tips for market successOptions provide a diverse, strategic, advantaged approach to trading that can significantly limit the overall risks of a trade or yield additional returns. For many people, investing in options seem so risky that they fail to capitalize on this potentially lucrative opportunity that can unlock doors you would never imagine. The Bloomberg Visual Guide to Options uses full-color charts and other illustrations to help readers understand the mechanics and actionable details of the marketplace and how to profit from options trading. An accessible reference volume for investment professionals of all levels of experience, the book takes a direct and to the point approach to the topic, enhanced by colorful and visually effective graphs and charts of the options market. Discussing the functions of the exchanges, how they work, and the strategies for taking advantage of the market while steering clear of risk, this is the ultimate visual guide to understanding the world of trading options. Immerses readers in the exciting world of options trading through the use of full-color graphs and chartsProvides tips, tricks, and real scenarios for successful trading, whether trading in a bull, bear, or neutral marketPresents detailed, unique strategies for understanding and succeeding in the real options marketIncludes special learning aids, such as Key Point Summaries, Do-It-Yourself Exercises, Step-By-Step Instructions, and much morePutting even the most complex options trading issues at your fingertips in an easy-to-understand, readily accessible format, Bloomberg Visual Guide to Options is a must-have trading reference for professional investors.
The world of options -- Tools and knowledge for trading options professionally -- Visualizing the greeks -- Visualizing basic strategies: trading calls and puts.
Includes index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Options (Finance); Options (Finances); BUSINESS & ECONOMICS -- Investments & Securities -- General; Options (Finance)